Hydrological connectivity of headwaters to downstream waters: introduction to the featured collection - Nadeau, T.L; Rains, M.C (Journal of the American Water Resources Association, 2007)
The SWAATCC case presented the Court with two issues: (1) whether an isolated water could be considered part of the "waters of the United States," protected under the Clean Water Act (CWA) - and thus subject to the U.S. Army Corps of Engineers' (Corps) regulatory authority under section 404 of the CWA - solely based on its use by migratory birds; and, if so, (2) whether Congress had the constitutional authority under the Commerce Clause to include these as waters of the United States. During that same time period, a significant majority of courts, including 17 appellate court decisions, concluded that SWANCC was narrowly focused on isolated waters, and did not change the jurisdictional status of tributaries or adjacent wetlands.